Medición de impedancia eléctrica de la piel en el rango de frecuencia de 5 a 1,000 Hz - Lizarde Araiza, H.; Muñoz Guerrero., R. (Revista Mexicana de Ingenieria Biomedica, 2007)
The skin has electrical properties that affect the quality of the bioelectrical signal when they are recorded by surface electrodes. The skin has electrical impedance due to its physical and physiological characteristics. In this paper, the results of skin impedance are represented in Cole-Cole graphics for A, B, C at a different time. The technique used for impedance measurement was the three electrodes applying a constant current in the frequency spectrum 5 to 1,000 Hz. The skin impedance was different of person to person (A, B, C). The skin impedance results were since 406.7K Ohms for 5 Hz to 23 K Ohms for 1,000 Hz. The electrodes were Ag/AgCl cup 9 mm diameter. The acquisition board was programmed in LabView 6.1.